2009
DOI: 10.1002/jor.20772
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia on glucose transport in primary equine chondrocytes in vitro and evidence of reduced GLUT1 gene expression in pathologic cartilage in vivo

Abstract: Articular chondrocytes exist in an environment lacking in oxygen and nutrients due to the avascular nature of cartilage. The main source of metabolic energy is glucose, which is taken up by glucose transporters (GLUTs). In diseased joints, oxygen tensions and glucose availability alter as a result of inflammation and changes in vascularisation. Accordingly, in this study we examined the effects of hypoxia and the hypoxia mimetic cobalt chloride (CoCl 2 ) on glucose transport in equine chondrocytes and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 36 publications
3
38
0
5
Order By: Relevance
“…It was previously reported that interference with proteoglycan glycosylation in the Golgi inhibits their secretion (Hameetman et al, 2007;Ratcliffe et al, 1985). HIF1 is known to regulate uptake and consumption of glucose, which is necessary for proteoglycan glycosylation (Mobasheri et al, 2002;Peansukmanee et al, 2009;Ren et al, 2008). This suggests that HIF1 may regulate not only collagen hydroxylation, but also proteoglycan glycosylation.…”
Section: Research Articlementioning
confidence: 99%
“…It was previously reported that interference with proteoglycan glycosylation in the Golgi inhibits their secretion (Hameetman et al, 2007;Ratcliffe et al, 1985). HIF1 is known to regulate uptake and consumption of glucose, which is necessary for proteoglycan glycosylation (Mobasheri et al, 2002;Peansukmanee et al, 2009;Ren et al, 2008). This suggests that HIF1 may regulate not only collagen hydroxylation, but also proteoglycan glycosylation.…”
Section: Research Articlementioning
confidence: 99%
“…The expression of HIF-1α and EPO-R were most often found in cancers with PR-/ER-/ /HER2+/ immunohistochemical profile (42.85%). opment of the existing vessels that are unable to supply oxygen to the intensely proliferating neoplastic tissue [9]. In solid tumors hypoxia is a result of growing metabolic activity and oxygen consumption by rapidly proliferating tumor cells and a drop in pH of surrounding environment [10].…”
Section: Resultsmentioning
confidence: 99%
“…EPO and its receptor (EPO-R) have recently been found to be expressed on several normal non-hematopoietic cells as well as in cancer tissues. Specifically, high expression of EPO-R has been found on the surface of endothelial cells and various solid tumors [9][10][11].…”
mentioning
confidence: 99%
“…Increased expression of GLUT 1 was demonstrated as a response to hypoxia in stem cells, adipocytes, neurons, astrocytes and chondrocytes [19]. Increased expression of GLUT 4 was observed in skeletal muscle cells and cardiomyocytes [20,21].…”
Section: The Role Of Hypoxia In Cancermentioning
confidence: 97%